ҚАРАҚАЛПАҚ ХАЛЫҚ АЙТЫСЛАРЫНДА АССОНАНС - Насирова, А.П. (SCIENCE and SOCIETY, 2023)
The article analyzes the linguistic and poetic features of the phenomenon of assonance in the Karakalpak folk aitys. The possibilities of creating an artistic image and expressing ideas are studied about the phenomenon of assonance with the help of examples.
Keywords: karakalpak folk aitys; poetic speech; linguopoetics; linguopoetical analysis; assonance phenomenon; vowel sounds; repetition of vowels; artistic image